Mangrove Carbon Potential in The Bagek Kembar Mangrove Area and Cemara Lembar South Coast, West Lombok - Rita Alawiyah; Abdul Syukur; Didik Santoso (Jurnal Biologi Tropis, 2026)
The mangrove ecosystem is one of the coastal ecosystems that plays an important role in climate change mitigation due to its ability to absorb and store large amounts of carbon, especially in sediments (below ground carbon). Sedimentary carbon is relatively stable and stored for a long period of time, making its presence an important indicator in blue carbon studies. This study aims to analyze the potential of mangrove sediment carbon storage in Bagek Kembar Village and Cemara Beach, Lembar Selatan Village, West Lombok Regency. The study was conducted from August to December 2025 using a quantitative descriptive method. Sediment sampling was carried out by purposive sampling in three mangrove zones, namely the front, middle, and back zones. In each zone, sediment samples were taken at three depth intervals, namely 0–30 cm, 30–60 cm, and 60–100 cm, resulting in a total of 18 samples analyzed. Analysis of organic matter and sediment carbon content was carried out using the Loss on Ignition (LOI) method, while bulk density was used as a physical parameter of the sediment for calculating sediment carbon stocks. The results of the study showed that the bulk density value of mangrove sediment in Bagek Kembar Village ranged from 0.51–0.62 g/cm³ with an average of 0.57 g/cm³, while at Cemara Beach, Lembar Selatan Village ranged from 0.44–0.69 g/cm³ with an average of 0.60 g/cm³. The carbon stock of mangrove sediment in Bagek Kembar Village was higher than that of Cemara Beach, Lembar Selatan Village. This difference was influenced by the density of mangrove vegetation, the organic matter content of sediment, as well as the environmental characteristics and water dynamics at each location. This study shows that both locations have good potential as sediment carbon stores and need to be managed sustainably.